A Baseline Study on Pattern of Helmet Use in the State of Rajasthan, India. (September 2017) - Mathur, Alok Kumar; Gupta, Shivam; Bandhu, Ashish
Head injuries sustained in the crash are the main cause of death and disability. Such deaths and disabilities can be prevented by consistent and correct wearing of a quality helmet. A baseline study was conducted to understand the pattern of helmet use in all 7 administrative divisional headquarters of state of Rajasthan in 2015. Among 1, 17, 553 two wheelers observed, almost two-fifth drivers (39.4%) wore helmet correctly, whereas, less than three-fifth (58.7%) did not. Almost equal percentage of male (58.6%) and female (58.9%) did not wear helmet at all. As compared to drivers, two-wheeler passengers were observed lower in using helmet correctly (11.6%). Even though correct helmet use during the crash reduces the severity of head and neck injury, observed helmet use in Rajasthan was low. Two-pronged strategy needs to be used by Government – First, Increased provision for awareness generation among community for helmet use by drivers and passengers through print media, electronic media, folk media, and social media. Second there must be provision of enforcement of the road traffic law by traffic police of Rajasthan. It would be required that the Government organizations, Corporate groups, and NGOs should come together and start helmet use in mission mode.